Struktur Naratif Seymour Chatman Dalam Kumpulan Cerpen Memburu Muhammad Karya Feby Indirani - Dwi Fernanda, Aviriyanto; Wilyanti, Liza Septa; Rahariyoso, Dwi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
This study aims to describe the narrative structure in the short story collection Memburu Muhammad by Feby Indirani by applying Seymour Chatman’s theoretical framework, which distinguishes between the components of story and discourse. The research is grounded in the need to understand how contemporary literary works construct meaning through narrative organization, particularly those addressing social, spiritual, and humanistic issues. The data consist of textual excerpts, events, actions, characters, and discourse elements found in five selected short stories Rahasia Rumah Kami, Bakso Terenak di Dunia, Dia Bertanya Tentang Tuhan, Kisah Cinta Azazil, and Melukis Tuhan, with the short story collection serving as the primary data source. Data were collected through close reading, observation, and note-taking, followed by systematic classification using Chatman’s analytical categories. The analysis employed a qualitative descriptive method by reducing data, identifying the structure of story and discourse, interpreting their narrative functions, and examining how both components interact to shape the thematic meaning of each story. Data validation was conducted through theoretical triangulation and referential adequacy to ensure the accuracy of interpretation. The results show that all five stories exhibit coherent story structures composed of kernels, character actions, events, characterizations, and settings, while their discourse elements appear through variations in narrative sequencing, flexible points of view, and symbolic-reflective linguistic style. These findings indicate that Feby Indirani successfully integrates story and discourse to create meaningful narratives that are communicative, aesthetically rich, and capable of encouraging readers to engage critically with moral, spiritual, and humanistic issues.